(untitled) (Ustozlar uchun, 2025)
This article examines the fundamental physiological mechanisms of nerve fibers and synapses, focusing on their structural organization, electrophysiological properties, and roles in neural communication. By integrating classical neurophysiology with modern experimental findings, the study analyzes the conduction of action potentials, the functional differences between myelinated and unmyelinated fibers, and the molecular events underlying synaptic transmission. Special attention is given to the generation and propagation of electrical impulses, synaptic vesicle cycling, neurotransmitter release, receptor activation, and synaptic plasticity. The paper highlights the importance of nerve fiber and synapse physiology in maintaining neural network function and its implications for understanding neurological disorders, neural development, and therapeutic interventions. The findings demonstrate that nerve fibers and synapses form the core communication system of the nervous system, allowing rapid, precise, and adaptable information transfer throughout the organism.¹